Interleukin-6 signalling mediates Galectin-8 co-stimulatory activity of antigen-specific CD4 T-cell response - Carabelli, Julieta (2018)
Galectin-8 (Gal-8) is a mammalian lectin endowed with the ability to co-stimulate antigen-specific immune responses. We have previously demonstrated that bone-marrow-derived dendritic cells produce high levels of interleukin-6 (IL-6) in response to Gal-8 stimulation. As IL-6 is a pleiotropic cytokine that has a broad effect on cells of the immune system, we aimed to elucidate whether IL-6 was involved in Gal-8-dependent co-stimulatory signals during antigen recognition by specific CD4 T cells. With this aim, splenocytes from DO11.10 mice were incubated with a low dose of the cognate ovalbumin peptide in combination with Gal-8. Interleukin-6 was found significantly increased in cultures stimulated with Gal-8 alone or Gal-8 plus cognate peptide. Moreover, IL-6 signalling was triggered during Gal-8-induced co-stimulation, as determined by phosphorylation of signal transducer and activator of transcription 3. Interleukin-6 blockade by neutralizing monoclonal antibody precluded Gal-8 co-stimulatory activity but did not affect the antigen-specific T-cell receptor activation. Different subsets of dendritic cells, as well as macrophages and B cells, were identified as the cellular source of IL-6 during Gal-8-induced co-stimulation. To confirm that IL-6 mediated the Gal-8 co-stimulatory effect, antigen-presenting cells from IL-6-deficient or wild-type mice were co-cultured with purified CD4 T cells from OTII mice in the presence of cognate peptide and Gal-8. Notably, Gal-8-induced co-stimulation, but not the antigen-specific response, was significantly impaired in the presence of IL-SL-6 signalling mediates the Gal-8 immune-stimulatory effect.